2009
DOI: 10.1111/j.1365-2222.2008.03102.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional and longitudinal association of the secretoglobin 1A1 gene A38G polymorphism with asthma phenotype in the Perth Infant Asthma Follow‐up cohort

Abstract: Background Associations between Clara cell secretory protein gene variants (SCGB1A1, also known as CC16, CC10, CCSP and uteroglobin) and the asthma phenotype have been found in five out of eight studies world-wide. No study has investigated the contribution of SCGB1A1 polymorphisms to the development and/or persistence of the asthma phenotype in a birth cohort followed over time.Objective The aim of this study was to determine the role of the SCGB1A1 gene in the development of the asthma phenotype. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 75 publications
1
28
0
Order By: Relevance
“…47,48 The A38G polymorphism in the promoter region of this gene decreases the amount of expressed CC16 and has been found to be associated with wheezing disorders in children and adults. 19,21,22,49,50 Taken together, these findings support the concept that CC16 can have an important role in the pathogenesis of these diseases.…”
Section: Discussionsupporting
confidence: 74%
“…47,48 The A38G polymorphism in the promoter region of this gene decreases the amount of expressed CC16 and has been found to be associated with wheezing disorders in children and adults. 19,21,22,49,50 Taken together, these findings support the concept that CC16 can have an important role in the pathogenesis of these diseases.…”
Section: Discussionsupporting
confidence: 74%
“…Although the slopes resulting from sensitivity analysis performed are not identical, they were similar, confirming the strength of the associations reported and the robustness of the data. The factors that influence levels of airway responsiveness during infancy are not fully understood, but previous studies suggest that genetic and environmental factors act in utero to determine initial airway structure and function [7,[20][21][22][23][24][25]. In addition, there is evidence that some immunogenetic factors responsive to environmental influences may contribute to airway responsiveness and asthma at 6 and 12 years, as shown in the PIAF study [22][23][24][25], and in later childhood, as shown in another childhood cohort [26].…”
Section: Discussionmentioning
confidence: 97%
“…The factors that influence levels of airway responsiveness during infancy are not fully understood, but previous studies suggest that genetic and environmental factors act in utero to determine initial airway structure and function [7,[20][21][22][23][24][25]. In addition, there is evidence that some immunogenetic factors responsive to environmental influences may contribute to airway responsiveness and asthma at 6 and 12 years, as shown in the PIAF study [22][23][24][25], and in later childhood, as shown in another childhood cohort [26]. Although this study was not specifically designed to describe the mechanisms by which airway responsiveness evolves through childhood, our findings may suggest that intrinsic or inherent levels of airway responsiveness determine asthma in early childhood and continue to affect respiratory outcomes throughout childhood, but with increasing age, exposure to environmental factors becomes the more dominant determinant of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…CC16, also known as homo sapiens secretoglobin, family 1A, member 1 (SCGB1A1), Clara cell 10 kDa protein (CC10) or Clara cell secretory protein (CCSP) (16)(17)(18), is secreted by non-mucous, non-ciliated airway epithelial cells (19,20). CC16 is the main component of the extracellular lining fluid of airways (21).…”
Section: Introductionmentioning
confidence: 99%